Обмеження здійснення права на належне батьківське виховання малолітніх осіб: сутність і критерії - Маковецька, Вікторія В.; Маковецька, В. В.; Makovetska, Viktoriia V.; Makovetska, V. V. (Одеса : Гельветика, 2020)
Стаття присвячена актуальній проблемі обмежень здійснення права на належне батьківське виховання малолітніх осіб. Такі обмеження зумовлені природними факторами: нездатністю чи складністю для дитини задовольнити більшість своїх потреб, адекватно усвідомлювати їх значення. Оціночний характер належності виховання зумовлений складністю визначення меж правомірної поведінки батьків відносно виховання. Обмеження здійснення цього права визначаються іншими правами дитини та правами батьків, які створюють відповідні умови або перешкоди, визначають виникнення чи здійснення його окремої правомочності, полягають у забороні автономного вчинення дій особою до 14 років. Доводиться, що задоволення інтересів дитини є можливим шляхом комплексного забезпечення її прав батьками, що й здійснюються ними. Здійснення права на належне виховання не обмежується лише можливостями отримання виховання через спеціальні педагогічні, психологічні прийоми, що зумовлює й інші обставини, які створюються при здійснені інших прав дитини або батьківських прав. Проаналізовано право виїзду дитини за кордон, яке має розцінюватися крізь призму найкращих інтересів дитини, а не рівності прав батьків, зважаючи на можливість зловживання ними правом на надання дозволу. При встановленні роздільного проживання дитини з одним із батьків встановлюється передбачене законом обмеження здійснення права на належне виховання. Запропоновано надати право дитині з десяти років ініціювати питання про своє місце проживання, якщо існує спір між батьками. Чинне законодавство не забороняє авторитарний і ліберальний стилі виховання, що зумовлює широкі межі батьківських прав у цій галузі і відповідає міжнародним стандартам, надає право дитині в якості самозахисту протидіяти неналежному вихованню, що відрізняється від непідкорення дитини батьківський владі. Зроблено висновок, що методи виховання можуть бути важливим критерієм для визначення місця проживання дитини, визначення способів участі у вихованні того з батьків, хто проживає окремо, а їх зміна – при поверненні дитини батькам, поновленні батьківських прав, затвердженні плану соціального супроводу сім’ї дитини тощо.

The article deals with the topical issue of limitations on exercising the right for proper parental nurturing of children under the age of 14. Such limitations are determined by natural factors: child’s inability to satisfy most of his or her needs, to adequately recognize their significance and conditions of satisfying them. The evaluative character of the propriety of nurturing is determined by the difficulty of defining the limits of parents’ lawful behavior concerning nurturing. Limitations on this right are influenced by the realization of other child’s and parent’s rights that create conditions or obstacles for its realization, determine the emergence or realization of its particular authority and lie in the fact that personally performing acts acting by a person under the age of 14 is prohibited or the realization of rights is delegated to the parents. It is proved that satisfaction of a child’s interests is possible in case of overall securing of his or her rights by the parents who have the respective responsibilities. Realization of the right is not limited to just a possibility of getting the nurturing through special methods and techniques, which makes it necessary to take into account other circumstances that arise during exercising other rights of a child or parents. A child’s right for going abroad is analysed. It must be assessed in terms of child’s best interests rather than the equality of parental rights as there is a possibility of parents’ abusing the right for giving permission. In case of establishing separate residence of a child less than 14 years with one of the parents there is a lawfully established limitation on exercising the right for proper nurturing. It is suggested that a child should be given the right to open an issue of his or her residence from the age of nine if there is a dispute between the parents. Current legislation carries a risk of improper nurturing through authoritative and liberal styles, which is determined by the wide limits of parental rights concerning nurturing but at the same time conforms with international standards. Opposition to improper nurturing, which is an attempt of self-defence, is different from child’s disobedience to parental authority. A conclusion is drawn that nurturing methods can be an important criterion for establishing a child’s place of residence and the ways of how the parent who lives separately participates in the nurturing, while changes in nurturing methods can be a criterion for returning the child to the parents, for restoration of parental rights, for confirming the plan of social support of a child’s family etc.
Маковецька В. В. Обмеження здійснення права на належне батьківське виховання малолітніх осіб: сутність і критерії / В. В. Маковецька // Юридичний вісник. - Одеса : Гельветика - 2020. - № 3. - С. 319-327.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; limitations on exercising the right for proper parental nurturing; the interests of the child; abuse of parental rights; proper forms and methods of upbringing; обмеження здійснення права на належне батьківське виховання; інтереси дитини; зловживання батьківськими правами; належні форми та методи виховання